Mitigation of Environmental Damage Through Natural Resources Management Contracts (Eco-Contract Perspective) - Firmanda, Hengki; Hibatul wafi, Mahmud; Syahrin, M. Alpi (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Environmental damage by extractive activities is caused by the formulation of policies that have not placed nature and the environment as legal subjects. Policy formulation in the form of a contract of work tends to accommodate human interests and is profit-oriented. This study aims to examine strategies for mitigating environmental damage caused by PT Freeport’s mining activities based on an eco-contract perspective. PT Freeport’s contract of work is the object of analysis in this research, while data on environmental damage are obtained from national media. Theoretical-reflective approach is used in analyzing the data to formulate mitigation strategies. The results showed that the mitigation of environmental damage in the eco-contract perspective emphasizes the natural relationships and interactions between all components of the ecosystem. In other words, mitigation of environmental damage requires equal treatment between the environment and humans which also indicates equal rights. In fact, force majeure conditions and natural disasters are still viewed from a human perspective, so that efforts to identify and socialize environmental damage only focus on human aspects rather than nature and the environment. PT Freeport’s contract of work has not accommodated mitigation efforts of environmental damage that ecologically oriented. In addition, the weak mapping, control, and socialization of PT Freeport’s mining activities have implications for the lack of efforts to mitigate environmental damage.